Perceptions And Practices Of Self-Medication Among The Residents Of Western, Nepal - Adhikari, Pharsuram (Journal of Manmohan Memorial Institute of Health Sciences, 2023)
Correction: On 27/11/2023 the PDF was replaced because of a mismatch in the introduction and methodology inside the article and the error is human error (copy / paste). Background: Self-medication is defined as the “The taking of drugs, herbs or some remedies on personal initiative, or on the advice of another person without consulting a physician for the aliment of self-diagnosed physical illness”. Self-medication is practiced throughout the world, including both developing and developed countries. Self-medication includes both risks and benefits. Objectives: To assess the perceptions and practices of self-medication among the residents of Western, Nepal. Methods: A cross-sectional study was conducted among 378 respondents aged above 18. Closed ended questionnaire was used as data collection tool. Non-probability purposive sampling method was used for the collection of data. Results: The prevalence of self-medication practices was found to be 76.8%. Friends/Family members/Relatives 34.20%), Past-own experience (23.9%) and Pharmacist (23.5%) were the major source of information for self-medication practices. The most common type of illness for self-medication were Headache (19.7%), Cough and Cold (19.1%) and fever (18.10%). NSAIDs (32.9%), Cough Syrups (15.0%) and Antibiotics (14.8%) were the mostly used drugs in self-medication practices. The most common reasons for self-medication were previous experience (23.59%), minor illness (19.77%) and quick reliefs (19.1%). More than half of respondents (57.0%) were found to have positive perception towards the self-medication practices. This study showed education status (p=0.033) had significant association with the self-medication practices. Conclusion: The study focused to assess the perception and practices of self-medication. The prevalence of self-medication was found to be 78.6%. More than half of the residents were found to possess positive perception towards the self-medication practices.